Peran Orang Tua Terhadap Anak-Anak Gifted - Erly Oviane Malelak; Joris Taneo (SOLIDARITY: Journal of Social Studies, 2021)
The research objective is to describe the role of parents towards gifted children. The type of research used is qualitative. The research subjects were 6 parents of gifted students. The data collection instruments used were interviews, observation and documentation study. The results showed that the role of parents includes love, nutrition and nutrition, and stimuli given from prenatal to childhood. Affection in the form of full attention, creates a comfortable atmosphere, accompanies and helps children learn. Nutrients and nutrients in the form of nuts, eggs, green vegetables, meat, fish, fruit, and exclusive breastfeeding for 2 - 3.5 years. The stimulus given is listening to music, reading, communicating verbally and non-verbally through touching or lightly stroking the mother's stomach that is done by the father and mother when the mother is pregnant, singing, inviting the fetus to talk, and inviting the fetus to pray. Tujuan penelitian adalah mendeskripsikan bagaimana peran orang tua terhadap anak-anak gifted. Jenis penelitian yang digunakan ialah kualitatif. Subjek penelitian ialah orang tua siswa gifted yang berjumlah 6 orang. Instrumen pengumpulan data yang digunakan ialah wawancara, observasi dan studi dokumentasi. Hasil penelitian menunjukkan bahwa peran orang tua meliputi kasih sayang, gizi dan nutrisi, dan stimulus yang diberikan sejak masa prenatal hingga masa kanak-kanak. Kasih sayang berupa perhatian penuh, menciptakan suasana nyaman, menemani dan membantu anak belajar. Gizi dan nutrisi berupa kacang-kacangan, telur, sayuran hijau, daging-dagingan, ikan, buah, dan ASI ekslusif hingga 2 - 3,5 tahun. Stimulus yang diberikan yakni memperdengarkan musik, membaca, berkomunikasi verbal dan non verbal melalui sentuhan atau elusan-elusan kecil pada perut ibu yang dilakukan ayah dan ibu ketika ibu mengandung, berdendang, mengajak janin berbicara, dan mengajak janin berdoa. Kata Kunci: peran, orang tua, anak-anak gifted